Studi Etnofarmasi Tumbuhan Berkhasiat Obat Suku Buton Sub Etnis Kalende - Hasty Hamzah; Mursalim Mursalim; Sapril Sapril (Jurnal Sains & Kesehatan, 2022)
This study aimed to find out various herbal plants of  Butonese Sub-Ethnic Kalende, in Kapontori sub district, Buton Regency, Sulawesi Tenggara. This study was a descriptive research using qualitative method and snowball sampling technic by interviewed 15 informants using questionnaire. This study had obtained 46 families of 72 habitus of herbal plants and one more that had not been identified yet. The most used herbal plants was from zingiberaceae family. Leaf is the most often used part of the herbal plants with the highest percentage (49%), which was processed by boiling it (43%). Those herbal plants could heal various disease.